METODE PICTURE AND PICTURE KARTU GRAFIK FUNGSI SEBAGAI MEDIA PEMBELAJARAN MATEMATIKA SISWA KELAS IX MADRASAH TSANAWIYAH NEGERI 1 LANGKAT - Ahmad Yuti (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2020)
The results of classroom action research (PTK) show that the value acquisition has increased very well, where the results of this study use quantitative data analysis with 32 respondents from class IX-1 as samples, while data management uses the product moment formula and the t test. Picture And Picture function graph card as a medium for learning mathematics for grade IX students at Madrasah Tsanawiyah Negeri 1 Langkat, it can improve student learning outcomes in mathematics, this can be seen from the results of daily exams, the correlation of arithmetic results in the first cycle between pre-test scores (pre-test) with the block I test score of 0.798, and the t test of 7.262, and the correlation of the calculated results in the second cycle between the block I test score and the block II test score of 0.899, and the t test of 11.26, it can also increase student activity in mathematics This can be seen from the activity of students in participating in the mathematics learning process with a value of 88% attendance at the beginning of the action, increased to 95% attendance in the first cycle, and increased again to 100% attendance in the second cycle, because students enjoy making and playing graphic cards. Function, so that it is fun for students in learning mathematics.Keywords: Picture and Picture Method, Function Graphic Card, Mathematics Learning Media